Understanding Past Earthquakes - Elliott, Austin; Gruetzner, Christoph; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book presents the state of the art in research on the characteristics of past earthquakes. It presents an overview of contemporary developments, their use cases, and practical considerations, with the aim of introducing readers to recently developed methodologies as well as the sources, derivation, and handling of their uncertainties. The disparate fields of seismology, stratigraphy, geomorphology, and geodesy are all being applied to the common goal of understanding past earthquakes, and in this realm, each has experienced significant advances in the 2010s. The contents cover contemporary methods in remote sensing geomorphology, forensic pre-instrumental seismology, historic macroseismology, and paleogeodesy, some of which are already being employed together to derive a holistic picture of seismic events past. This book compiles in one resource the respective explanations of the diverse array of tools which are being used in the 2020s to investigate past seismic events to expand our seismic record. .
Introduction -- Modern Approaches to Understanding Past Earthquakes -- Measuring Ground Motions -- Historical Instrumental Seismology -- Eyewitness Macroseismology -- Shaking Constraints from Geology and the Natural Landscape -- Measuring Ground Deformation -- Remote Sensing of Surface Terrestrial Rupture Length and Slip -- Paleogeodesy of Offshore Earthquakes from Coral Microatolls. - Submarine Rupture extents and Sizes from Seafloor Coring -- Synthesizing Observations of Individual Earthquakes -- Surface Rupture Geometries, Slip Variability & Scaling Relations from Multiple Earthquakes -- Extrapolating Paleoseismic Parameters to an Entire Fault -- Distribution of Deformation through the Earthquake Cycle -- Synoptic Conclusion -- Employing and Combining Diverse Approaches to Understand Past Earthquake Ruptures in Relation to Modern Seismic Events.
Keywords: Natural disasters; Geology; Sedimentology; Natural Hazards; Geology; Sedimentology